Profil Pekerja Pemanen Kelapa Sawit Bagian Cutting Egrek - Risma Karlina Prabawati; Erna Lidiana (Universitas Muhammadiyah Purwokerto, 2021)
Musculoskeletal Disorders (MSDs) is a label for the perception of pain or pain in the musculoskeletal system. MSDs can be caused by the equipment, techniques, and activities performed during work. Harvesters who use manual techniques or cutting egrek have the potential risk for MSDs as a result of an ergonomic work attitude and posture. This study aims to determine the profile of oil palm harvesters using cutting egrek techniques. This research is a descriptive research with the survey method. Samples were obtained by systematic random sampling method, amounting to 82 people. The data used in this study are primary data and secondary data. Most CuE technique oil palm harvesters were at the age of 41-50 years, working period of 6-10 years, and with a work posture that needed immediate improvement, and 76.8% suffered from MSDs complaints. So that it is necessary to have immediate intervention from companies and workers to reduce the risk of MSDs complaints in the future, especially in posture and work techniques.